Caracterización de mezclas de mortero de cal y arena, compatibles con morteros patrimoniales y su incidencia en las propiedades mecánicas de la mampostería de arcilla cocida, en edificaciones históricas (2018)
In many countries, especially in Europe, different investigations have been developed, related with fire clay masonry built with lime mortars, used in ancient buildings. These structures have high cultural values, and they must be preserved. Nevertheless, sometimes these constructions present structural problems due to natural factors or incorrect human actions, making necessary the search of new reinforcement systems that improve the resistance of buildings, reducing architectural modifications in the original project. This document presents the characterization of lime mortars, compatibles with ancient mixes and their incidence in mechanical properties of fire clay masonry. This work proposes two methods for non-invasive reinforcement, trying to improve the mechanical behavior of masonry.